2020
DOI: 10.1152/ajpcell.00342.2019
|View full text |Cite
|
Sign up to set email alerts
|

Female sex and Western-style diet protect mouse resistance arteries during acute oxidative stress

Abstract: A Western-style diet (WD; high in fat and carbohydrates) increases vascular oxidative stress. We hypothesized that vascular cells adapt to a WD by developing resilience to oxidative stress. Male and female C57BL/6J mice (4 wk of age) were fed a control diet (CD) or a WD for 16–20 wk. Superior epigastric arteries (SEAs; diameter, ~125 µm) were isolated and pressurized for study. Basal reactive oxygen species production was greatest in SEAs from males fed the WD. During exposure to H2O2 (200 μM, 50 min), propidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(51 citation statements)
references
References 56 publications
6
45
0
Order By: Relevance
“…MDA is the end product of lipid peroxidation and is an essential biochemical parameter used as an oxidative stress marker. Both the ketogenic diet and the western diet were reported to affect oxidative stress (Norton et al, 2020). In the present study, it was observed that feeding with short-term KD caused increases in antioxidant parameters in the liver.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…MDA is the end product of lipid peroxidation and is an essential biochemical parameter used as an oxidative stress marker. Both the ketogenic diet and the western diet were reported to affect oxidative stress (Norton et al, 2020). In the present study, it was observed that feeding with short-term KD caused increases in antioxidant parameters in the liver.…”
Section: Discussionsupporting
confidence: 54%
“…Although the physiological mechanisms of these diets on organs are not well understood, both experimental and human studies have shown that obesity is associated with increased oxidative stress markers and lipid peroxidation (Wilson et al, 2007). In the studies examining the effects of feeding with WD; unlike KD, WD has been reported to increase oxidative stress (Jenkins et al, 2016;Norton et al, 2020). Irregularity of hepatic lipogenesis and prolonged exposure of the heart to a high fuel supply have been shown to be important causes of heart failure in rats fed with high-fat WD (Harmancey et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not detect changes in Nos3 mRNA, it is not known whether NO production or bioavailability was altered. Interestingly, greater resistance to oxidant stress has been reported in endothelial cells of rodents pre‐conditioned with HF diet, which may protect against endothelial dysfunction. It also was reported that ischaemia itself blunts vasodilatory responses within the microvascular networks of post‐ischaemic muscle .…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 4, 2021. ; https://doi.org/10.1101/2021.08.02.454805 doi: bioRxiv preprint 28 dying cells (14,15). Following BaCl2 exposure, respective nuclear dyes (in standard PSS) were perfused through the lumen of a cannulated SEA (0.1 mL/min) or superfused over the surface of an endothelial tube for min followed by min wash in standard PSS.…”
Section: Cell Deathmentioning
confidence: 99%